Geographic Distribution of Regional Quota Program Graduates of Japanese Medical Schools: A Nationwide Cohort Study - Matsumoto, Masatoshi; Kashima, Saori; Owaki, Tetsuhiro; Iguchi, Seitaro; Inoue, Kazuo; Tazuma, Susumu; Maeda, Takahiro (Academic medicine, 2019)
To show the practice location of graduates from two Japanese programs recruiting physicians to rural areas: a regional quota program of medical schools and a prefecture scholarship program (a prefecture is an administrative geographic division). Graduates of each program must work in a designated rural prefecture for a fixed period. A nationwide cohort study was conducted for three groups of participants graduating between 2014 and 2016: quota graduates without scholarship (quota alone), nonquota graduates with scholarship (scholarship alone), and quota graduates with scholarship. A questionnaire was sent via medical school or prefecture office to each potential subject to collect baseline individual data, including home prefecture and graduation year. Data were connected through physician identification number to the Physician Census 2016 of the Ministry of Health, Labour and Welfare to identify the subjects' practice location and compared with data for other physicians in the census. Comparisons were conducted with Mann-Whitney and chi-square tests. The proportion of physicians working in nonmetropolitan municipalities for quota alone (185/244; 75.8%), scholarship alone (305/363; 84.0%), and quota with scholarship (341/384; 88.8%) was significantly higher than for other physicians (13,299/22,906; 58.1%). Median population density of the municipalities where subjects worked for quota alone (1,042.4 persons per square kilometer), scholarship alone (613.5), and quota with scholarship (547.4) was significantly lower than that for other physicians (3,214.0). These disparities increased with number of years since graduation. The regional quota and prefecture scholarship programs succeeded in producing physicians who practiced in rural areas of Japan.